(untitled) (Research, Society and Development, 2020)
This research was developed as a mandatory requirement for completion of the Pedagogy course of the Lapa Educational College - FAEL, in the Tijucas Pole, Santa Catarina, Brazil, in 2019. For this article, we sought to add new reflections further enriching the work in relation to the interactions and games experienced in the spaces of Early Childhood Education. According to the National Curriculum Guidelines for Early Childhood Education (DCNEI, 2009), interactions and games are structuring axes of pedagogical practice developed with children in early childhood. The objective of this study is to understand the importance of games and interactions for child development, discussing the organization of spaces as a potential for interactions and games and for child protagonism. To support the proposed objectives, we sought to analyze how educators are developing their pedagogical practices for the promotion of interactions and games at the Municipal Center of Early Childhood Education (CMEI) Mauri Afonso da Silva, located in the municipality of Tijucas, State of Santa Catarina, Brazil. To achieve the proposed objectives, we outlined the methodological paths that supported our investigation. Thus, this research has a qualitative character, with an approximation to field research. With this it was possible to observe and analyze the phenomena experienced by the daily research. For the discussion on the importance of spaces for child protagonism, we sought a theoretical deepening with the contributions of Piaget, Vygotsky, Wallon, Friedmann, Zabalza, Horn, among others, who helped to think and reflect the theme presented.